2022
DOI: 10.1002/pon.6072
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and bowel cancer screening participation

Abstract: Objective To better understand barriers to participation in mail‐out bowel cancer screening programs, two survey studies tested the relationship between psychological distress and self‐reported bowel cancer screening. Methods First, a nationally representative sample of Australians N = 5421 completed measures of bowel cancer screening and psychological distress (using the Kessler Psychological Distress Scale; K10). Second, N = 479 completed a survey measuring participation in the National Bowel Cancer Screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is therefore important not to interpret results as a comprehensive review of general anxiety and cancer screening. One recent study not captured in the current review showed that in two large samples, sub‐clinical levels of trait anxiety and psychological distress were positively associated with bowel cancer screening, but those reporting extreme symptoms were less likely to screen 17 . Curvilinear relationships were not tested in any of the studies in the current review, however an inverted U effect might be a plausible model to describe the relationship between anxiety and cancer screening, as originally proposed by Hailey (1991) in relation to breast cancer screening 107 .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…It is therefore important not to interpret results as a comprehensive review of general anxiety and cancer screening. One recent study not captured in the current review showed that in two large samples, sub‐clinical levels of trait anxiety and psychological distress were positively associated with bowel cancer screening, but those reporting extreme symptoms were less likely to screen 17 . Curvilinear relationships were not tested in any of the studies in the current review, however an inverted U effect might be a plausible model to describe the relationship between anxiety and cancer screening, as originally proposed by Hailey (1991) in relation to breast cancer screening 107 .…”
Section: Discussionmentioning
confidence: 69%
“…One recent study not captured in the current review showed that in two large samples, sub-clinical levels of trait anxiety and psychological distress were positively associated with bowel cancer screening, but those reporting extreme symptoms were less likely to screen. 17 Curvilinear relationships were not tested in any of the studies in the current review, however an inverted U effect might be a plausible model to describe the relationship between anxiety and cancer screening, as originally proposed by Hailey (1991) in relation to breast cancer screening. 107 This is supported by other recent research showing that people with extreme or pathological psychological distress may be less likely to participate in cancer screening.…”
Section: Study Limitationsmentioning
confidence: 94%
See 3 more Smart Citations